Implementation Of Clean And Healthy Living Behaviour In Raya Village, Berastagi District, Karo Regency - R. Hamdani Harahap; Yeni Absah; Farid Aulia (Jurnal Scientia, 2024)
The implementation of clean and healthy living behavior through the empowerment of BUMDes (Village-Owned Enterprises) management faces several challenges. These include: the limited capacity of BUMDes management to optimize partnerships, the low knowledge of BUMDes managers about clean and healthy living behavior practices, and the inadequate capacity of village officials in organizing partnerships and waste management to maintain and implement clean and healthy living behaviors, such as maintaining environmental cleanliness from organic and non-organic waste. This condition requires follow-up through community service programs. These activities aim to empower BUMDes managers and the community in adopting clean and healthy living behaviors. The objectives of this community service program are to help reduce partnership problems, enhance the knowledge of BUMDes managers as key drivers of tourism area development, improve their ability to manage village resources to boost the local economy, and strengthen the capacity of village officials in organizing partnerships and business management while promoting clean and healthy living behaviors. To achieve these objectives, the methods used in this program include: socialization and training on the implementation of clean and healthy living behaviors, participatory organization, and monitoring and evaluation. The outcomes of this socio-economic empowerment initiative include enabling the partner group (BUMDes management of Raya Village) to act as a driving force for the community, leveraging social capital, and sustainably developing BUMDes. This contributes to the overall improvement of community welfare through the enhancement of BUMDes operations.